Proposal, project, practice, pause: developing a framework for evaluating smart domestic product engagement - Woodall, Tony; Rosborough, Julie; Harvey, John (Springer, 2017)
Smart homes are fast becoming a reality, with smart TVs, smart meters and other such “smart” devices/systems already representing a substantial household presence. These, which we collectively term “smart domestic products” (SDPs), will need to be promoted, adopted, and normalized into daily routines. Despite this, the marketing canon lacks a substantive discourse on pertinent research. We look to help correct this by melding ideas from organizational sociology, innovation diffusion and appropriation studies, and service dominant logic. Consequently, we suggest a framework for research that responds directly to the specific characteristics of SDPs. Using the SDP eco-system as a context, our framework emphasizes the interplay of embeddedness, practice, value and engagement. It comprises a four-stage horizontal/longitudinal axis we describe as proposal, project, practice and pause. Cross-sectionally we focus on value, and combine aspects of existing thought to suggest how this impacts each stage of our engagement continuum. We subsequently identify perceived personal advantage as the resultant of these two axes and propose this as the key for understanding consumer and SDP sociomaterial engagement. This article also advances a definition of SDPs and ends with an agenda for further research.